PENGARUH METODE MIND MAPPING TERHADAP HASIL BELAJAR IPS PADA SISWA KELAS V DI SDN 1 BATUJAI - Aji, M. Valian Aji Sukma; Nurhasanah, Nurhasanah; Oktaviyanti, Itsna (Jurusan Ilmu Pendidikan FKIP Universitas Mataram, 2023)
This strudy aims to determine the effect of using the mind mapping method on the learning outcomes of fifth grade students at SDN 1 Batujai Academic Year 2022/2023. This research is a quantitative study with a research design non-equivalent control group design quasi-experimental type. The population in the studywere all fifth grade students at SDN 1 Batujai Academic year 2022/2023, while the samplesinthe study wereVA class students as the experimental class and VB class students as the control class. The sampling teacnique used was saturated sampling. Data collection techniquesusing test and observation. The data analysis technique uses the One Way ANOVA test with SPSS 21.0 calculation which shows that the significance value is 0.846>0.050, the H0 is accepted and Ha is rejected. So the results of this study indicate that there is no effect of the mind mapping learinng method on the learning outcomes of fifth grade students at SDN 1 Batujai Academic Year 2022/2023